A phase I study of S-1 and cisplatin with concurrent hypofractionated carbon-ion radiotherapy for patients with stage III non-small cell lung cancer - Miura, Yosuke; Kubo, Nobuteru; Sunaga, Noriaki; Okano, Naoko; Tsurumaki, Hiroaki; Kawamura, Hidemasa; Sakurai, Reiko; Maeno, Toshitaka; Hisada, Takeshi; Ohno, Tatsuya (Frontiers in Oncology, 2025)
ObjectivesWe conducted a phase I study to evaluate the recommended dose of S-1 in combination with cisplatin (SP) and concurrent carbon ion radiotherapy (CIRT) in patients with stage III locally advanced non-small cell lung cancer (LA-NSCLC).Materials and methodsS-1 was administered orally twice daily after a meal for 14 consecutive days, and cisplatin was administered on days 1 and 8. The dose of each drug in this study was planned as follows: level 0, S-1–30 mg/m2 twice daily and cisplatin 40 mg/m2; level 1, S-1–40 mg/m2 twice daily and cisplatin 40 mg/m2. CIRT was conducted at a total dose of 64 Gy (relative biological effectiveness) in 16 fractions.ResultsSix patients were enrolled in this study. At level 1, one patient experienced grade 3 elevated alanine aminotransferase and aspartate aminotransferase levels, which is regarded as a dose-limiting toxicity. This event improved immediately. Five patients developed grade 2 esophagitis. In three of the five patients, symptoms such as pain and dysphagia due to esophagitis recurred several months after resolution of the acute esophagitis that occurred during irradiation. None of the patients experienced adverse events of ≥grade 3. Thus, level 1 was determined to be the recommended dose.ConclusionChemotherapy with SP and concurrent CIRT is feasible and well-tolerated in patients with Stage III LA-NSCLC.